Physical Properties of Estrus Mucus in Relation to Conception Rates in Dairy Cattle - Hyun-Joo Lim; Jun-Kyu Son; Ho-Beak Yoon; Kwang-Soo Baek; Tae-il Kim; Yeon-Sub Jung; Eung-Gi Kwon (The Korean Society of Animal Reproduction and Biotechnology, 2014)
The study aimed to determine the physical characteristics of estrus mucus and conception rates in dairy cattle. Samples of estrus mucus from the cervix were collected from 108 dairy cattle during heat and were examined for color and consistency. Samples were taken from bred animals at starting from day of breeding to the completion of one estrus cycle. The color of the cervical mucus was studied based on its transparency while the consistency was based on the thinness and thickness of the cervical mucus. The dairy cattle were bred and the pregnancy diagnosis was performed at the 60th day post breeding. Findings showed that the estrus mucus of the dairy cattle was transparent in 58.3%, turbid in 31.5% and dirty in 10.2%. It was further observed that the mucus consistency of the dairy cattle was thin in 74.1% and thick in 25.9%. In the pregnant group, 67.3% mucus samples were found transparent, turbid in 23.6% and dirty in 9.1%. However, the corresponding figures for the non-pregnant group had 49.1%, 39.6% and 11.3%. The consistency of cervical mucus was found to be thin in 74.1% and thick in 25.9% of dairy cattle. The conception rates of dairy cattle with thin and thick consistency of cervical mucus were 81.8% and 18.2%, respectively. Pregnant was associated with consistency of cervical mucus (p<0.05). Findings indicated that dairy cattle with thin consistency of cervical mucus and had clear discharge were pregnant cows.